Unraveling haplotype errors in the DFNA33 locus - Vona, Barbara; Regele, Sabrina; Rad, Aboulfazl; Strenzke, Nicola; Pater, Justin A.; Neumann, Katrin; Sturm, Marc; Haack, Tobias B.; Am Zehnhoff-Dinnesen, Antoinette G. (Frontiers in Genetics, 2023)
Genetic heterogeneity makes it difficult to find causal genes for hearing loss. Studies from previous decades have mapped numerous genetic loci, providing critical supporting evidence for gene discovery studies. Despite widespread sequencing accessibility, many historically mapped loci remain without a causal gene. The DFNA33 locus was mapped in 2009 that coincidentally contains ATP11A, a gene recently associated with autosomal dominant hearing loss and auditory neuropathy type 2. In a rare opportunity, we genome sequenced a member of the original family to determine whether the DFNA33 locus may also be assigned to ATP11A. We identified a deep intronic variant in ATP11A that showed evidence of functionally normal splicing. Furthermore, we re-assessed haplotypes from the originally published DFNA33 family and identified two double and one triple recombination events in the pedigree, a highly unlikely occurrence, especially at this scale. This brief research report also serves as a call to the community to revisit families who have previously been instrumental to gene mapping studies, to provide closure, and resolve these historical loci.